Road Safety Data In Africa : A Proposed Minimum Set of Road Safety Indicators for Data Collection, Analysis, and Reporting - Segui Gomez, Maria (Washington, DC: World Bank, 2022)
Road safety in Africa remains a big challenge. Globally, Africa has the highest fatality rate of all the continents, despite having the lowest motorization rate and smallest road infrastructure network. Through the Global Plan for the Decade of Action (2011-2020), the African Road Safety Action Plan, the African Road Safety Charter, and the targets set out in the Sustainable Development Goals (SDGs), Africa has made strong commitments to improve road safety outcomes on the continent. However, documents assessing the magnitude of the problem show that there exists a need to address it by implementing effective and efficient interventions, which require determination, professional qualification, and personnel and economic resources. In order to make informed decisions on effective interventions to mitigate this challenge, a deeper analysis of the road safety-related environment in the region is required. This document outlines a process that began in 2017 to define a common set of indicators to be collected, analyzed, and monitored by African countries, as part of their efforts to improve road safety in Africa.